Modified CaO Catalyst from Golden Snail Shell (Pomacea canaliculata) for Transesterification Reaction of Used Cooking Oil - Siti Rodiah; Desti Erviana; Fachtur Rahman; Anissa Widya Budaya (Al-Kimia, 2020)
One of alkaline earth metal oxide is calcium oxide, CaO has more attention because it has high strength, low solubility in methanol, and can be synthesized from sources that are easy to obtain. One of the sources of CaO and showed its catalytic properties was the golden snail shell. In this study, synthesize ash golden snail shell modified with fly ash leached and non-leached as a source of silicate (SiO2) has been investigated. The CaO/fly ash catalyst was applied to the transesterification reaction of used cooking oil. There are three catalysts have synthesized, namely golden snail shell calcined (CK), 75% golden snail shell calcined modified by 25% fly ash (CKFA), and by 25% fly ash leached (CKFAL). Based on the results of characterization with spectrophotometer X-Ray Diffraction (XRD), golden snail shell calcined at 900 ˚C containing 93.94% Ca (OH)2. Modified CaO catalyst from golden snail shell and fly ash were active to convert used cooking oil become biodiesel.